ON AAG history - James, Preston E; Martin, Geoffrey J (The Professional Geographer, 1979)
The seventy-fifth anniversary of the Association of American Geographers is a time to celebrate. To set the tone for the anniversary meetings in Philadelphia, I asked Geoffrey Martin, Marvin Mikesell, and John Adams to discuss significant events in the AAG's past, the Association’s present state, and prospects for the future. Their presentations were made in the initial session of the meetings on Sunday evening, April 22. We are pleased to reproduce for the members of the Association the transcripts of those verbal presentations. We are indebted to each of these colleagues for the excellent start they provided for our largest-ever professional meeting.—Brian J. L. Berry, President. © 1979 by the Association of American Geographers.
Keywords: dept.egm

Review: Climate and Human Ecology. Jim Norwine, ed. - Yacher, Leon (Professional Geographer, 1979)
Keywords: dept.egm